2021
DOI: 10.2147/idr.s313485
|View full text |Cite
|
Sign up to set email alerts
|

Carriage, Risk Factors, and Antimicrobial Resistance Patterns of Salmonella Isolates from Raw Beef in Jimma, Southwestern Ethiopia

Abstract: Purpose Consumption of raw beef infected with multidrug-resistant Salmonella is pertinent to the world public health risk of antimicrobial resistance. Henceforth, this study aimed to investigate the carriage, antimicrobial resistance (AR) patterns, and the revealing risk factors of Salmonella-contaminating beef in abattoirs and butcher shops in Jimma town. Methods A cross-sectional study was conducted to investigate the carriage and AR patterns and to reveal the risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Resistance against kanamycin, sulfadimethoxine-trimethoprim, tetracycline, nalidixic acid, and chloramphenicol reported in this study is consistent with others. 40,41 Antimicrobial resistance in Salmonella isolated from various livestock and products have been reported in Ethiopia 15,16,42,43 and elsewhere in the world, 44 suggesting the global occurrence of resistance. Continued use of the same antimicrobials could exert selection pressure on resistant bacteria, favoring their global distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance against kanamycin, sulfadimethoxine-trimethoprim, tetracycline, nalidixic acid, and chloramphenicol reported in this study is consistent with others. 40,41 Antimicrobial resistance in Salmonella isolated from various livestock and products have been reported in Ethiopia 15,16,42,43 and elsewhere in the world, 44 suggesting the global occurrence of resistance. Continued use of the same antimicrobials could exert selection pressure on resistant bacteria, favoring their global distribution.…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies have revealed widespread occurrence of Salmonella in chicken, cattle, camels, sheep, goats, humans, foodstuffs, and the environment. 13,14 Resistance to various antimicrobials has been reported in Salmonella isolated from beef 15 and milk. 16 Since broiler meat is the secondmost popular meat in the world, accounting for around 36% of total meat production, 17 there is a dire need to develop better understanding and assist poultry stakeholders to reduce Salmonella and delay development of resistance to antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…Infection rates with Salmonella spp. isolated from raw meat were found to be high in Jimma, south-western Ethiopia 42 Gondar, Ethiopia 43 and Wolaita Sodo, southern Ethiopia. 44 A similar investigation in Jimma found a significant incidence of E. coli and multidrug-resistant (MDR) E. coli O157:H7 in slaughterhouse and butcher meat.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, underreporting of cases and the prevalence of other diseases considered high priority may mask the problem of foodborne infections. 59 A study in Jimma, South West Ethiopia, 60 Gondar, Ethiopia 61 and Wolita Sodo, South Ethiopia 62 showed high carriage rates of Salmonella spp., isolated from raw beef. The same study, conducted in the same area, showed high rates of E. coli and multidrug resistant (MDR) E. coli O157:H7 in meat from abattoirs and butchers.…”
Section: Zoonotic Foodborne Bacteriamentioning
confidence: 99%